PENGARUH MORALITAS APARAT DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PEMERINTAH KOTA SURABAYA) - Widjajanti, Arie; Wahyuni, Wiwin (Liability, 2019)
The accounting fraud can happen anywhere and anytime, generally accounting fraud relating to corruption. Within the scope of government, fraud is very detrimental to the public interest. This research is aimed to explore the perceptions of employeesing overn mentagencies regarding the influence of morality apparatus and asymmetry of information on the trend of accounting fraud. This research is a population with four respondents consisting of head and staff sub-section of the finances and sub-section of the public and personneline very government agencies Surabaya. This research uses a sampling technique in total sampling. Date was collected by using a questionnaire. Data analysis methods used in this research is multiple regression with the help of SPSS 16.The results showed that: 1) morality apparatus and asymmetry of information simultaneously significant effect on the tendency of accounting fraud, 2) morality apparatus partially significant effect on the tendency of accounting fraud and information asymmetry does not significantly influence the tendency of accounting fraud.